Missed Opportunities : Innovation and Resource-Based Growth - Maloney, William F. (World Bank, Washington, DC, 2012)
The article discusses the 20th century opportunities for rapid natural resource-based growth that Latin America systematically missed. Even if it were the case that resource abundant countries have experienced relatively slow growth, the more interesting question is why some -Australia, and Sweden for example -successfully and rapidly developed while others did not. . Latin America seemed unable to follow their lead. Latin America's underperformance, and its particularly virulent strain of dependency, are in substantial measure due to impediments to technological adoption and innovation arising from weak national "learning" capacity, and the perverse incentives of the protectionist era.